2014
DOI: 10.2474/trol.9.121
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Sliding Wear Behaviour of Aluminium Matrix Composites with Hybrid Reinforcements for Automotive Applications

Abstract: The aluminium matrix composites, particularly with hybrid reinforcements are the advanced materials that have been widely used as a substitute material in the transport sector, to manufacture lighter-weight and higher-performance components. As these components are often subjected to sliding wear under working conditions, therefore several of these applications require enhanced frictional and wear resistance. The purpose of the current review is therefore aimed at highlighting the focus of the current research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…This phenomenon can be controlled by the addition of Gr particles in the Al/SiC composites, which smears the counterface and reduces the wear rate of the hybrid composites. This phenomenon was confirmed in the micrographs of the worn surfaces of Al/SiC/Gr composites, which revealed the presence of mild wear [76][77][78].…”
Section: Surface and Subsurface Behaviormentioning
confidence: 62%
“…This phenomenon can be controlled by the addition of Gr particles in the Al/SiC composites, which smears the counterface and reduces the wear rate of the hybrid composites. This phenomenon was confirmed in the micrographs of the worn surfaces of Al/SiC/Gr composites, which revealed the presence of mild wear [76][77][78].…”
Section: Surface and Subsurface Behaviormentioning
confidence: 62%
“…Moreover, the use of stir casting technique for fabrication of AMCs reduces the cost the composites, as it is economical, simple to perform and highly productive method [3,10]. Nowadays, there is growing concern in the production of HAMCs with better physical and mechanical properties [11,12]. Recent research investigations have revealed that agro/industrial waste materials such as fly ash, graphite, rice husk ash, etc., can be successfully used as a complementary reinforcement in AMCs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum MMCs are most popularly used composites because of its lightweight nature, high thermal conductivity, improved elastic modulus, and strength. 1 Aluminum alloy grades like LM25 were extensively used in automobiles because of their attractive characteristics such as good strength-to-weight ratio, high cast-ability, and good formability. LM25 alloy wheel rims of an automobile were tested under different load conditions, which resulted in optimized weight, shape with good factor of safety.…”
Section: Introductionmentioning
confidence: 99%